Temporal fluctuations in scale counts and body proportions of Amazonian riparian lizards (Cnernidophorus, Sauria, Teiidae) - Vanzolini, P. E. (Amazoniana, 2001)
Abrupt but short-lived changes in the number of ventral rows of scales and of dorsal granules, as well as in relative length of tail, tibia and head, were found in widely separated riverine populations of Amazonian Cnemidophorus, both parthenogenetic and . The explanation adopted is that offered by CARSON (1985) for a similar case in Hawaiian Drosophila: presence of considerable intra-clonal variability and sensitivity to stabilizing selection.
Keywords: Mudanças Abruptas